(untitled) (Journal of Misan Researches, 2025)
The current research is concerned with studying the relationship between drama in general and theater in particular with theories of psychology, and aims to review some of the literature to show how drama and theater writers benefit from the concepts, theories and laws that psychologists have arrived at through their works At the same time, the research represents an attempt to reveal the psychological effects of drama by referring to some studies that dealt with the role of drama in satisfying the psychological needs of individual viewers, whether they are in childhood, adolescence, or youth, and finally how to benefit from the research through the recommendations that can be provided. Related to the field of drama and theatre